2021
DOI: 10.1177/14614448211026575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pandemic lockdown on Fridays for Future’s hashtag activism

Abstract: Social movement organizations (SMOs) increasingly rely on Twitter to create new and viral communication spaces alongside newsworthy protest events and communicate their grievance directly to the public. When the COVID-19 pandemic impeded street protests in spring 2020, SMOs had to adapt their strategies to online-only formats. We analyze the German-language Twitter communication of the climate movement Fridays for Future (FFF) before and during the lockdown to explain how SMOs adapted their strategy under onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
4
33
0
2
Order By: Relevance
“…The results from our and related studies are mixed news for the movement, as they suggest that the pre-COVID-19 momentum was close to maximum capacity. There is evidence suggesting that the emotional basis of the movement shows signs of erosion (de Moor et al, 2020), and that the COVID-19-related lockdowns may have harmed the momentum persistently (Haßler et al, 2021). Our results suggest that the climate protest movement also not spills over easily from the youth to the adult population, at least in the German sample we studied.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The results from our and related studies are mixed news for the movement, as they suggest that the pre-COVID-19 momentum was close to maximum capacity. There is evidence suggesting that the emotional basis of the movement shows signs of erosion (de Moor et al, 2020), and that the COVID-19-related lockdowns may have harmed the momentum persistently (Haßler et al, 2021). Our results suggest that the climate protest movement also not spills over easily from the youth to the adult population, at least in the German sample we studied.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, recent evidence suggests that COVID-19 left a footprint in the communication structure by shifting the relative emphasis given to non-functional information(Haßler et al, 2021).24 Evidence from two different protest movements in Spain collected bySabucedo et al (2017) suggests that concerns of justice are important be for protestors. The inter-generational justice component in climate action suggests that this might also important for climate protesters, at least the young cohorts, but direct evidence on this is lacking.…”
mentioning
confidence: 99%
“…Similar to this research, the study of Haßler et al (2021) centered on a particular policy, with Twitter as its research locale, and observed how SMOs continued their engagement on Twitter. The work of Haßler et al (2021) also considered the role of hashtags in information dissemination and mobilization. Thus, the claim that the ongoing pandemic affected the activism of SMOs and individuals is only strengthened.…”
Section: Dominant Themes Pertinent To the Discussion Of Anti-terroris...mentioning
confidence: 77%
“…Meanwhile, the Philippine Independence Day is a national holiday that supposedly celebrates freedom which was perceived as the opposite of the potential threats to human rights which the Anti-Terrorism Bill can potentially engender. Haßler et al (2021) observe that social movement organizations (SMOs) shifted their engagements online when street protests became undoable because of the COVID-19 pandemic. Similar to this research, the study of Haßler et al (2021) centered on a particular policy, with Twitter as its research locale, and observed how SMOs continued their engagement on Twitter.…”
Section: Dominant Themes Pertinent To the Discussion Of Anti-terroris...mentioning
confidence: 99%
See 1 more Smart Citation